Verses of Prohibition for Children: Perspectives from Tafsir Ibn Kathir and Tafsir Al-Azhar and Their Relevance to the Field of Educational Psychology - Jihad, Hanif Ruhul; Shobahiya, Mahasri; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Children need a safe environment to explore and offer the support they need to learn and help them grow and develop. When children are curious about something, they will choose to explore it. Prohibitions expressed by parents to their children not to do something by saying "don't" can close down a child's initiative and creativity. Islam explains methods of raising children through various verses in the Qur'an. This research aims to describe the verses of the Qur'an in the form of prohibitions on children based on the Tafsir Ibn Kathir and Tafsir Al-Azhar, compare the meaning of the prohibitive verses in those two tafsirs and describe the impact of the prohibitions on children based on the two tafsirs in child educational psychology point of view. This research uses qualitative methods with library research that specifically examines prohibited verses for children in the context of educational psychology. The research results show that contemporary child psychology, which reveals that prohibitions aimed at children can close down the power of initiative, does not apply to several prohibitive verses in the Qur'an because they contain the fundamental value of monotheism. If the prohibition is not enforced, it will have more negative effects.